Studies on Synthesis of N-1 Fused Heterocyclic Derivatives Using Potassium Carbonate and PEG- 400 as Green Catalyst - Wanegaonkar, Anjali M.; Bhitre, Milind J. (Technological Innovation in Pharmaceutical Research Vol. 10, 2021)
Due to their synthetic utility and extensive variety of pharmacological effects, indole and benzimidazole, as well as their substituted derivatives, help to draw interest. The N-substituted fused heterocyclic compounds are usually physiologically active and could be employed as antitumor medicines. The various reactions reported that reactions of K2CO3 showing its essentiality for a particular reaction due to its characteristics like solubility in water, mild base character, easy availability, eco-friendly, and nontoxic in nature. In the presence and absence of phase transfer catalyst such as PEG-400 and TEBAC, the effect of the ratio of catalyst used anhydrous K2CO3 for its N-1 alkylation or arylation of indole-3-carboxaldehyde and 2-acetylbenzimidazole is observed. The ratio 1:4 of anhydrous K2CO3 along with PEG-400 gives, ease of catalyst handling, mild reaction conditions and reactions carried out at 10-15ºC temperature with excellent yields. The simplicity of the approach makes it attractive for the synthesis of N-fused heterocyclic derivatives that could be employed as biological substitutes.